Merging Assistance Function with Task Distribution Model to Enhance User Performance in Collaborative Virtual Environment - Khalid, S.; Ullah, Sehat; Alam, A. (The Nucleus, 2016)
Collaborative Virtual Environments (CVEs) falls under Virtual Reality (VR) where two or more users manipulate objects collaboratively. In this paper we have made some experiments to make assembly from constituents parts scattered in Virtual Environment (VE) based on task distribution model using assistance functions for checking and enhancing user performance. The CVEs subjects setting on distinct connected machines via local area network. In this perspective, we consider the effects of assistance function with oral communication on collaboration, co-presence and users performance. Twenty subjects performed collaboratively an assembly task on static and dynamic based task distribution. We examine the degree of influence of assistance function with oral communications on user’s performance based on task distribution model. The results show that assistance functions with oral communication based on task distribution model not only increase user performance but also enhance the sense of copresence and awareness.